2018
DOI: 10.1038/s41567-018-0056-5
|View full text |Cite
|
Sign up to set email alerts
|

Topological domain walls in helimagnets

Abstract: A magnetic helix arises in chiral magnets with a wavelength set by the spin-orbit coupling.We show that the helimagnetic order is a nanoscale analog to liquid crystals, exhibiting topological structures and domain walls that are distinctly different from classical magnets. Using magnetic force microscopy and micromagnetic simulations, we demonstrate that -similar to cholesteric liquid crystals -three fundamental types of domain walls are realized in the helimagnet FeGe. We reveal the micromagnetic wall structu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 41 publications
6
87
0
Order By: Relevance
“…(19) similar to the case of µ in Eq. (14). Experimentally it is found that λ 2 /λ 1 ≈ 0.14, although both terms are nominally of sixth order in λ SOC .…”
Section: Mca Potential Of Skyrmion Lattice Rotationmentioning
confidence: 92%
“…(19) similar to the case of µ in Eq. (14). Experimentally it is found that λ 2 /λ 1 ≈ 0.14, although both terms are nominally of sixth order in λ SOC .…”
Section: Mca Potential Of Skyrmion Lattice Rotationmentioning
confidence: 92%
“…Instead, considering that Lorentz microscopy probes the in‐plane magnetic induction rather than the in‐plane magnetization, the zig‐zag wall contrast and, to some extent, the fractal‐like contrast can be explained by a changing lattice orientation of the helical spins that generates a magnetization divergence and stray fields. Such a contrast was specifically visualized with magnetic force microscopy in B20 FeGe crystals at helix lattice boundaries [ 60 ] that lack a net in‐plane magnetization.…”
Section: Figurementioning
confidence: 99%
“…While topological spin textures are sometimes randomly dispersed as either defects or excited states [15,21,22], they can also be densely packed and described in terms of superposition states of spin spirals with propagation vectors q that define multi-q states [12,16,[23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%